Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s13068-015-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential of lipid metabolism in marine diatoms for biofuel production

Abstract: BackgroundDiatoms are an ecologically relevant group of microalgae that are not commonly considered for bio-oil production even if they are responsible for massive blooms at sea. Seventeen diatom species were screened for their capacity to produce biomass and lipids, in relation to their growth rate. Triglyceride levels were also assessed as a preferential source of biofuels.ResultsUsing statistical analysis, two centric diatoms, Thalassiosira weissflogii and Cyclotella cryptica, were selected as good candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 52 publications
5
78
2
1
Order By: Relevance
“…It has been reported that vitamin B 12 highly accelerates growth of a marine centric diatom, T. pseudonana [81]. Interestingly, neither growth rate nor TAG content of C. gracilis were affected by vitamin elimination; moreover, both growth and TAG accumulation here were superior in C. gracilis , compared with many other phytoplankton, including other diatoms [9]. Although there remains a possibility of contributions by coexisting microbes, C. gracilis was cultivated here without expensive vitamins, which would substantially reduce cultivation costs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It has been reported that vitamin B 12 highly accelerates growth of a marine centric diatom, T. pseudonana [81]. Interestingly, neither growth rate nor TAG content of C. gracilis were affected by vitamin elimination; moreover, both growth and TAG accumulation here were superior in C. gracilis , compared with many other phytoplankton, including other diatoms [9]. Although there remains a possibility of contributions by coexisting microbes, C. gracilis was cultivated here without expensive vitamins, which would substantially reduce cultivation costs.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, diatoms are responsible for nearly one-quarter of the annual global photosynthetic production of organic matter, which is nearly equal to the proportion attributed to tropical rain forests [6, 7]. In many diatomaceous species, assimilated carbon is accumulated in cells as triacylglycerol (TAG) that accounts for 25–45% of their cell dry weight [8, 9], while their silica shell makes up 40–78% of their weight [10]. In addition, diatoms contain many types of fatty acids (FAs) and related organic molecules [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…b (d'ippolito et al, 2015). c (Yongmanitchai and Ward, 1992;Plouguerné et al, 2014;d'ippolito et al, 2015;da Costa et al, 2016). d (Volkman et al, 1998;Viegelmann et al, 2014).…”
Section: Lipids and Fatty Acids In Diatomsunclassified
“…This is because using microalgae for biofuel production would have fewer adverse effects on food supply and other agriculture [4,5] as…”
Section: Introductionmentioning
confidence: 99%